Konflik Identitas Melahirkan Surat Kabar: Sejarah Surat Kabar Mandailing Tahun 1923 di Kota Medan - Ayu Astuti Ayu; Pujiati; Warjio (Badan Riset dan Inovasi Nasional (BRIN), 2023)
This article discusses one of the newspapers that was born during the Dutch colonial period in Medan City, namely the Mandailing Newspaper which was published in 1923. Through historical method and approach, the results of the research show that the presence of the Mandailing Newspaper was based on the conflict between the Batak and Mandailing ethnic groups which then gave birth to each group as a follower. Batak ethnic and some others choose Mandailing ethnicity. Those who joined Mandailing then founded the Mandailing Newspaper, spearheaded by Abdoellah Lubis. The initial aim of establishing the Mandailing Newspaper was to fight the concept of Batak ethnicity. However, in its development, this newspaper also reported on foreign issues, advice, independence ideas and the Islamic world. It is called the Mandailing Newspaper because this Mandailing newspaper is a newspaper whose role is to convey or channel the voices of the community and specifically Mandailing people wherever they are, especially in Medan. In this way, the Mandailing Newspaper contributed to the coloring of press activities during that period in Medan City. Keywords: Ethnic, Medan City, and Mandailing Newspaper.